Design, simulation and measurement of a post slot waveguide antenna - Lim, K.-S.; Koo, V.-C.; Lim, T.-S. (Taylor & Francis Group, 2007)
The need for flexibility in array design and more accurate control over the slot radiation level has led to the design of post slot antenna. A post slot waveguide antenna consists of a centreline longitudinal slot with a tuning post. By varying the probe depth and slot length, it is possible to produce beam steering effect electromechanically. The objective of this paper is to propose a novel post slot configuration for waveguide antenna design. The desired operating frequency is 1.4 GHz for L-band remote sensing application. This paper presents the simulation and measurement of the proposed post slot waveguide antenna. Simulation on a four-element of conventional shunt slot and the proposed post slot antenna arrays has been carried out by using a three-dimensional electromagnetic simulation tool. It is shown that the post slot array antenna has superior performance as compared to the conventional shunt slot array antenna in terms of first side-lobe level. A series of measurement on two hardware prototypes (proposed post slot and conventional shunt slot array antennas) has been conducted in an indoor anechoic chamber. The measurement results clearly indicate the flexibility of the proposed post slot in controlling radiation pattern as compared to the conventional shunt slot configurations.